Parental Perceptions of Child Vulnerability in Families of Youth With Spina Bifida: the Role of Parental Distress and Parenting Stress. (26th October 2017) - Driscoll, Colleen F Bechtel; Stern, Alexa; Ohanian, Diana; Fernandes, Nerissa; Crowe, Autumn N; Ahmed, S Samaduddin; Holmbeck, Grayson N
Abstract: Objective: This longitudinal study aimed to investigate parental distress and parenting stress in relation to parental perception of child vulnerability (PPCV) in youth with spina bifida (SB). Methods: Parents of 140 youth with SB (ages 8–15 years at Time 1) were recruited as part of a longitudinal study; data were collected at two time points, spaced 2 years apart. Mothers and fathers completed questionnaires assessing levels of personal distress, parenting stress, and PPCV. Results: Mothers and fathers reported similar levels of personal distress, parenting stress, and PPCV, but reports of PPCV increased over time. For mothers, both personal distress and parenting stress were significantly associated with PPCV cross-sectionally, but not longitudinally. For fathers, there were significant cross-sectional and longitudinal associations between parenting stress and PPCV. The cross-sectional association between maternal parenting stress and PPCV was moderated by age, with a significant association only for older youth. Conclusions: For parents of youth with SB, personal distress, and parenting stress are related to parental perceptions of child vulnerability, and child age may moderate this relationship. Parental personal distress and parenting stress are important targets for future interventions.